HALAL RESTAURANTS AND PORK FREE CONCEPT AWARENESS AMONG YOUNG MUSLIMS IN KOTA KINABALU, SABAH - Faridah Mohd Shah; Mimi Zarina Bakri, (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2024)
Halal is an Arabic term that means "permissible" or "lawful" in Islam. It is used to describe what is allowed or permitted according to Islamic dietary laws and other aspects of life. One of the issues in Sabah that seem endless is the halal issue of a restaurant and the issue of Muslims often going to restaurants that do not have a halal certificate and only have the label "Serve No Pork" or "Muslim Friendly". This has become a hot topic that is often discussed by the local community because they think there are still people who ignore the importance of eating at restaurants that are believed to be halal and toyyiban. This paper places its emphasis on young Muslims, as we hold the belief that the perspectives of youthful consumers, especially within the Muslim community, will shape the future of the Halal industry in our nation. Although there is not a single dataset that measures the awareness of pork-free versus halal concepts across Malaysia, but the general trend in Malaysia indicates a steady rise in both halal-certified businesses and consumer awareness. Data will be gathered through questionnaires sent to young Muslims in Kota Kinabalu, Sabah. This study employs quantitative methods to analyse and ascertain the degree of awareness and knowledge among young Muslims regarding the concept and practices of Halal. The survey data was analysed using the Statistical Package for the Social Sciences (SPSS). The statistical findings of this study aim to explain the level of awareness and knowledge of Muslim youth in Kota Kinabalu regarding the consumption of Halal products, especially in restaurants or eating places. The results showed a negative correlation between halal awareness, and other variables signals potential challenges or areas for improvement in halal perception, strategies, and education in Kota Kinabalu, Sabah.